Strategi Value Delivery Process pada Pemasaran Digital di Sektor Publik - Hasan, Pupung Puad; Hurriyati, Ratih; Dirgantari, Puspo Dewi (Jurnal Wacana Kinerja: Kajian Praktis-Akademis Kinerja dan Administrasi Pelayanan Publik, 2023)
The purpose of this study is to find out how the digital marketing process in public sector organizations is carried out and also to find out how public sector organizations deliver value (value delivery process) through digital marketing processes, especially through social media platforms, and what strategies are most appropriate for public organizations in delivering value. The digital marketing process studied in this study was carried out at the National Civil Apparatus Competency Mapping and Training Center (Puslatbang PKASN) National Institute of Public Administration Republic of Indonesia. To find out the digital marketing process carried out by the Puslatbang PKASN LAN, a social media analysis was carried out using the infact social media analytic application. The results of the analysis found that the digital marketing process through social media has not really been carried out effectively and optimally. This is illustrated by the results the Instagram account @puslatbang_pkasn which shows that the value is 1.04 posts per month and engagement is 0.01, which means it is still low and content is dominated by ceremonial content. Then to determine the most appropriate strategy in carrying out the value delivery process, an analysis was carried out using the analytical hierarchy process (AHP) method. The experts involved in filling out the AHP method amounted to 5 experts who were experts in public sector marketing and social media influencer. The results of the analysis with AHP found that social media platforms in order of priority: Instagram 0.78, Facebook 0.14, and Twitter 0.06. Meanwhile, the best content in delivering value is educational content of 0.48, program info content of 0.20, Q&A content of 0.14 and the rest is quiz content, popular memes and ceremonial content.